Carboxylated cellulose nanocrystal cryogel monoliths: a multi-tool study of morphology and porosity of pure and magnetite nanoparticle-decorated CNC scaffolds - Chen, Xining; Andrews, Mark P. (Frontiers in Soft Matter, 2023)
Tissue scaffolds are known to benefit from incorporation of nanoscale bio-additives like cellulose nanocrystals (CNC), which can affect porosity as an important tunable design parameter for bio-based scaffolds. In this paper, we probe how freeze-casting of carboxylated cellulose nanocrystals and CNC derivatized with magnetite nanoparticles yields macroscale cryogel scaffold monoliths. Cryogel topographical features and macropore morphologies depend on the conditions under which ice formation takes place, and on exposure to static magnetic fields. We examine porosity over several length scales with scanning electron microscopy (SEM) coupled with Local Thickness Euclidean distance image processing, small angle X-ray scattering (SAXS), and dynamic vapor sorption (DVS). SAXS data fitted with a mass fractal model and power law suggest that CNC particles aggregate to form well-defined compact walls in the range of 96.7–27.3 nm for all samples, while inclusion of Fe3O4 nanoparticles disrupts this compactness in the range of 27.3–4.8 nm. Analysis of DVS reveals that nanoparticles directly impact water uptake by the cryogel scaffolds and can reduce water sorption in mesopores with a radius of 5–6 nm.